3D CFD simulation and parametric study of a flat plate deflector for vertical axis wind turbine - Wong, Kok Hoe; Chong, Wen Tong; Poh, Sin Chew; Shiah, Yui-Chuin; Sukiman, Nazatul Liana; Wang, Chin-Tsan (Renewable energy, 2018)
Three-dimensional numerical simulations have been performed to analyze the aerodynamic characteristics of a straight-bladed NACA0021 vertical axis wind turbine (VAWT). The unsteady flow CFD simulation was validated with the wind tunnel experiment data available in the literature. Sliding mesh method with the SST k-ω turbulence model was employed to simulate the rotational motion of the VAWT using ANSYS Fluent. The study showed a good agreement between the simulation and the wind tunnel testing. Further simulations were carried out to study the effects of a flat plate deflector being placed at the upwind of the VAWT by varying a few parameters including the position, the inclination angle and the length of the flat plate deflector. The simulations showed that the augmented flow occurred at the near wake region where the flow was accelerated and deflected by the deflector before impinging with the turbine; hence the coefficient of power (CP) of the VAWT improved significantly. However, the performance of the VAWT was highly dependent on the position of the deflector. From the simulation results, with the optimum parameters, the cycle-averaged coefficient of torque was increased about 47.10% higher compared to the VAWT without the deflector. •Numerical simulations were performed on a straight-bladed VAWT with a flat plate deflector.•Parametric analysis of the flat plate deflector.•VAWT performance enhancement by the flat plate deflector as power augmentation device.